Polycyclic aromatic hydrocarbons—induced ROS accumulation enhances mutagenic potential of T‐antigen from human polyomavirus JC. Issue 11 (25th July 2013) - Wilk, Anna; Waligórski, Piotr; Lassak, Adam; Vashistha, Himanshu; Lirette, David; Tate, David; Zea, Arnold H.; Koochekpour, Shahriar; Rodriguez, Paulo; Meggs, Leonard G.; Estrada, John J.; Ochoa, Augusto; et al.
Abstract Polycyclic aromatic hydrocarbons (PAHs) are the products of incomplete combustion of organic materials, which are present in cigarette smoke, deep‐fried food, and in natural crude oil. Since PAH‐metabolites form DNA adducts and cause oxidative DNA damage, we asked if these environmental carcinogens could affect transforming potential of the human Polyomavirus JC oncoprotein, T‐antigen (JCV T‐antigen). We extracted DMSO soluble PAHs from Deepwater Horizon oil spill in the Gulf of Mexico (oil‐PAHs), and detected several carcinogenic PAHs. The oil‐PAHs were tested in exponentially growing cultures of normal mouse fibroblasts (R508), and in R508 stably expressing JCV T‐antigen (R508/T). The oil‐PAHs were cytotoxic only at relatively high doses (1:50–1:100 dilution), and at 1:500 dilution the growth and cell survival rates were practically unaffected. This non‐toxic dose triggered however, a significant accumulation of reactive oxygen species (ROS), caused oxidative DNA damage and the formation of DNA double strand breaks (DSBs). Although oil‐PAHs induced similar levels of DNA damage in R508 and R508/T cells, only T‐antigen expressing cells demonstrated inhibition of high fidelity DNA repair by homologous recombination (HRR). In contrast, low‐fidelity repair by non‐homologous end joining (NHEJ) was unaffected. This potential mutagenic shift between DNA repair mechanisms was accompanied by a significant increase in clonal growth of R508/T cells chronically exposed to low doses of the oil‐PAHs. Our results indicate for the first time carcinogenic synergy in which oil‐PAHs trigger oxidative DNA damage and JCV T‐antigen compromises DNA repair fidelity. J. Cell. Physiol. 228: 2127–2138, 2013. © 2013 Wiley Periodicals, Inc.